Legal Certainty and Arbitration in Indonesia: Striking a Balance Between Efficiency and Substantive Justice (Indonesian Court and Justice Review, 2024)
Arbitration has become an increasingly preferred dispute resolution mechanism in Indonesia due to its efficiency, confidentiality, and finality. However, concerns remain regarding its ability to ensure substantive justice and legal certainty. This study examines the Indonesian arbitration framework, focusing on the tension between procedural efficiency and the delivery of fair outcomes. Using doctrinal analysis and selected case studies, the research evaluates the enforcement of arbitral awards, judicial intervention in arbitration proceedings, and the legal standards applied by courts when reviewing arbitration-related matters. The findings indicate that while Indonesia’s Arbitration Law provides a clear legal basis for arbitral independence and finality, inconsistent judicial interpretation and limited oversight mechanisms can lead to uncertainty and unpredictability. This raises critical questions about how to ensure justice without undermining the core efficiency values of arbitration. The novelty of this study lies in its effort to bridge the normative objectives of arbitration with the evolving expectations of justice in complex commercial disputes. As arbitration continues to expand within Indonesia’s legal landscape, especially in cross-border matters, striking a balance between speed and fairness becomes increasingly urgent. The study contributes to policy debates by offering recommendations to strengthen legal certainty, improve judicial consistency, and enhance the integrity of the arbitration process without compromising its core advantages.